Association between ambient air pollution and colorectal cancer risk: The Multiethnic Cohort Study - Ugonna Ihenacho; Chiuchen Tseng; Jun Wu; Scott Fruin; Timothy V. Larson; Salma Shariff-Marco; Loïc Le Marchand; Daniel O. Stram; Brian Z. Huang; Lynne R. Wilkens; Christopher A. Haiman; Beate Ritz; et al. (Environmental Research, 2026)

Relationships among peri-traumatic circulating endocannabinoids and long-term, negative outcomes following traumatic injury - Emily A. Albertina; Carissa W. Tomas; Timothy J. Geier; Sydney C. Timmer-Murillo; Isela G. Pina; Kelley Jazinski-Chambers; Garrett Sauber; Jacklynn M. Fitzgerald; Christine L. Larson; Terri A. deRoon-Cassini; Cecilia J. Hillard (Psychopharmacology, 2026)
Rationale Traumatically injured individuals can develop chronic negative psychological sequelae. Improved understanding of contributing, peri-traumatic risk factors is essential to reduce the risk of these consequences. Previous studies have found that peri-traumatic, circulating endocannabinoid concentrations are positively associated with development of post-traumatic stress disorder (PTSD), chronic pain and depression months later, particularly in members of racial/ethnic groups that have been historically marginalized. Objectives This replication study examined relationships among peri-trauma serum endocannabinoid concentrations and long-term consequences in a cohort comprised primarily of individuals from marginalized racial and ethnic groups. Methods Participants ( n = 100; 81% from marginalized racial and ethnic groups) were traumatically injured adults presenting to the ED of an urban tertiary care hospital. Endocannabinoids N -arachidonoylethanolamine (AEA) and 2-arachidonoylglycerol (2-AG) were measured in serum collected within days (peri-trauma) and 6–10 months following injury (follow-up). Assessments, including PTSD, depression, pain and quality of life were completed. Statistical approaches, including multivariate, hierarchical regressions, were used to determine associations among serum endocannabinoid concentrations and long-term outcomes. Results Although it did not survive correction for multiple comparisons, peri-trauma serum 2-AG concentrations. Peri-trauma serum 2-AG concentrations were also positively associated with PTSD, pain severity, and functional engagement scores at follow-up. There were no significant associations between circulating 2-AG or AEA and depression. Conclusions These findings generally replicate earlier studies demonstrating that serum 2-AG concentrations are biomarkers of risk for PTSD and pain and uncover an additional association with poor functional quality of life. Further studies are needed to determine the underlying mechanisms of these relationships.

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Age, growth, and reproductive biology of Achilles tang (Acanthurus achilles) around Hawai'i Island, USA - Timothy B. Grabowski; Richard Masse; Dawn McSwain; Annie Larson; Lillian J. Tuttle Raz; Eva Schemmel; Danielle E. Bartz; Nikola Rodriguez (Environmental Biology of Fishes, 2025)

Limitations of existing park quality instruments and suggestions for future research - KangJae “Jerry” Lee; Myla F.J. Aronson; Jeffrey A.G. Clark; Fushcia-Ann Hoover; Hogyeum Evan Joo; Peleg Kremer; Daniele La Rosa; Kelli L. Larson; Christopher A. Lepczyk; Susannah B. Lerman; Dexter H. Locke; Charles H. Nilon; et al. (Landscape and Urban Planning, 2024)

Quantifying the contributions of road and air traffic to ambient ultrafine particles in two urban communities - Chunliang Wang; Jianbang Xiang; Elena Austin; Timothy Larson; Edmund Seto (Environmental Pollution, 2024)

Discussion: Prioritize perennial grain development for sustainable food production and environmental benefits - Lee R. DeHaan; James A. Anderson; Prabin Bajgain; Andrea Basche; Douglas J. Cattani; Jared Crain; Timothy E. Crews; Christophe David; Olivier Duchene; Jessica Gutknecht; Richard C. Hayes; Fengyi Hu; et al. (Science of The Total Environment, 2023)

Assessing the effectiveness of portable HEPA air cleaners for reducing particulate matter exposure in King County, Washington homeless shelters: Implications for community congregate settings - Ching-Hsuan Huang; Thu Bui; Daniel Hwang; Jeffry Shirai; Elena Austin; Martin Cohen; Timothy Gould; Timothy Larson; Igor Novosselov; Shirlee Tan; Julie Fox; Edmund Seto (Science of The Total Environment, 2023)

Coastal response to global warming during the Paleocene-Eocene Thermal Maximum - Glenn R. Sharman; Jacob A. Covault; Peter P. Flaig; Regan Dunn; Preston Fussee-Durham; Toti E. Larson; Timothy M. Shanahan; Kalli Dubois; John B. Shaw; James L. Crowley; Barry Shaulis (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Particulate matter, traffic-related air pollutants, and circulating C-reactive protein levels: The Multiethnic Cohort Study - Meera Sangaramoorthy; Juan Yang; Chiuchen Tseng; Jun Wu; Beate Ritz; Timothy V. Larson; Scott Fruin; Daniel O. Stram; Sung-shim Lani Park; Adrian A. Franke; Lynne R. Wilkens; Jonathan M. Samet; et al. (Environmental Pollution, 2023)

The phylogeny and global biogeography of Primulaceae based on high-throughput DNA sequence data - Drew A. Larson; Andre S. Chanderbali; Olivier Maurin; Deise J.P. Gonçalves; Christopher W. Dick; Douglas E. Soltis; Pamela S. Soltis; Peter W. Fritsch; James J. Clarkson; Aurélie Grall; Nina M.J. Davies; Isabel Larridon; et al. (Molecular Phylogenetics and Evolution, 2023)

Exposure assessment for air pollution epidemiology: A scoping review of emerging monitoring platforms and designs - Sun-Young Kim; Magali N. Blanco; Jianzhao Bi; Timothy V. Larson; Lianne Sheppard (Environmental Research, 2023)

Corrigendum: Associations between cyanobacteria and indices of secondary production in the western basin of Lake Erie - James H. Larson; Mary Anne Evans; Robert J. Kennedy; Sean W. Bailey; Keith A. Loftin; Zachary R. Laughrey; Robin A. Femmer; Jeff S. Schaeffer; William B. Richardson; Timothy T. Wynne; J. C. Nelson; Joseph W. Duris (Limnology and Oceanography, 2022)
In the last year, we became aware that data used in our above‐referenced manuscript from 2018 published in Limnology and Oceanography contained significant errors. In the 2018 manuscript, we found that indices of secondary production were negatively correlated to indices of cyanobacterial abundance and toxicity. Unfortunately, one of our indices of cyanobacterial abundance (biovolume) and our measurement of toxicity (microcystin concentration) were inaccurate in the data we used in the 2018 manuscript. Upon discovering these errors, we immediately began correcting the repositories where these data were available. Having corrected those data repositories, we are now reporting on the re‐analysis of the data using the methods previously described in the 2018 manuscript. Although the relationships are slightly different, our interpretation is that the conclusions of the 2018 manuscript are still valid using the corrected data. The data errors we experienced were traced to a spreadsheet that was used to share data among the research team, which had errors caused by mistakes in copy‐pasting formulas instead of data and ‘inadvertent’ edits that were saved by the spreadsheet's auto‐save function. We apologize to the scientific community for these errors.

Fine-Scale Air Pollution Models for Epidemiologic Research: Insights From Approaches Developed in the Multi-ethnic Study of Atherosclerosis and Air Pollution (MESA Air) - Kipruto Kirwa; Adam A. Szpiro; Lianne Sheppard; Paul D. Sampson; Meng Wang; Joshua P. Keller; Michael T. Young; Sun-Young Kim; Timothy V. Larson; Joel D. Kaufman (Current Environmental Health Reports, 2021)

Preface for the Special Issue of IJRS Drones section in conjunction with the 6th UAS4Enviro conference - Anita Simic Milas; Timothy A. Warner; Nicolas H. Younan; Ivan Balenovic; Matthew D. Larson (International Journal of Remote Sensing, 2019)

Habitat explains patterns of population decline for an invasive crayfish - Eric R. Larson; Timothy A. Kreps; Brett Peters; Jody A. Peters; David M. Lodge (Ecology, 2019)
Invasive nonindigenous species are defined by their impacts: they substantially change native communities or ecosystems. Accordingly, invasive species might transform their habitats in ways that eventually become unfavorable to them, causing population declines or even extirpations. Here we use over 40 yr of systematically collected data on the abundance of the invasive rusty crayfish Faxonius rusticus from 17 lakes in northern Wisconsin, USA to explore whether population declines of this invader are related to the prevalence of rocky habitat, which shelters crayfish from predators and is unchanged by crayfish. We predicted that lakes with rock‐dominated substrates would be resistant to F. rusticus population declines, whereas lakes lacking rock‐dominated substrates would experience F. rusticus declines due to crayfish destruction of shelter‐providing macrophytes. We found that in nearly one‐half (47%) of the study lakes, F. rusticus experienced population declines over the study time period, and these lakes had significantly lower proportions of rock substrate than lakes that did not experience population declines. We recommend that more studies should investigate the potential for invasive species‐mediated community or ecosystem feedbacks to eventually contribute to their own population declines.

Associations between cyanobacteria and indices of secondary production in the western basin of Lake Erie - James H. Larson; Mary Anne Evans; Robert J. Kennedy; Sean W. Bailey; Keith A. Loftin; Zachary R. Laughrey; Robin A. Femmer; Jeff S. Schaeffer; William B. Richardson; Timothy T. Wynne; J. C. Nelson; Joseph W. Duris (Limnology and Oceanography, 2018)
Large lakes provide a variety of ecological services to surrounding cities and communities. Many of these services are supported by ecological processes that are threatened by the increasing prevalence of cyanobacterial blooms which occur as aquatic ecosystems experience cultural eutrophication. Over the past 10 yr, Lake Erie experienced cyanobacterial blooms of increasing severity and frequency, which have resulted in impaired drinking water for the surrounding communities. Cyanobacterial blooms may impact ecological processes that support other services, but many of these impacts have not been documented. Secondary production (production of primary consumers) is an important process that supports economically important higher trophic levels. Cyanobacterial blooms may influence secondary production because cyanobacteria are a poor‐quality food resource and cyanotoxins may be harmful to consumers. Over 3 yr at 34 sites across the western basin of Lake Erie, we measured three indices of secondary production that focus on the dominant bivalve taxa: (1) growth of a native unionid mussel, (2) the size of young‐of‐year dreissenid mussels, and (3) the mass of colonizing animals on a Hester‐Dendy sampler. Associations between these indices and cyanobacterial data were estimated to assess whether cyanobacteria are associated with variation in secondary production in the western basin of Lake Erie. The results suggest cyanobacterial abundance alone is only weakly associated with secondary production, but that cyanotoxins have a larger effect on secondary production. Given recurring late‐summer cyanobacterial blooms, this impact on secondary production has the potential to undermine Lake Erie's ability to sustain important ecosystem services.

Chemical characterization and in vitro toxicity of diesel exhaust particulate matter generated under varying conditions - Julie Richman Fox; David P. Cox; Bertram E. Drury; Timothy R. Gould; Terrance J. Kavanagh; Michael H. Paulsen; Lianne Sheppard; Christopher D. Simpson; James A. Stewart; Timothy V. Larson; Joel D. Kaufman (Air Quality, Atmosphere & Health, 2015)

Systolic blood pressure changes in indigenous Bolivian women associated with an improved cookstove intervention - Donee Alexander; Timothy Larson; Susan Bolton; Sverre Vedal (Air Quality, Atmosphere & Health, 2015)

Stable chlorine isotope behavior during volcanic degassing of H2O and CO2 at Mono Craters, CA - Jaime D. Barnes; Timothy J. Prather; Miguel Cisneros; Kenneth Befus; James E. Gardner; Toti E. Larson (Bulletin of Volcanology, 2014)

Population pharmacokinetic and exposure-response analysis of nilotinib in patients with newly diagnosed Ph+ chronic myeloid leukemia in chronic phase - Richard A. Larson; Ophelia Q. P. Yin; Andreas Hochhaus; Giuseppe Saglio; Richard E. Clark; Hirohisa Nakamae; Neil J. Gallagher; Eren Demirhan; Timothy P. Hughes; Hagop M. Kantarjian; Philipp D. le Coutre (European Journal of Clinical Pharmacology, 2012)

Interactions between auditory and somatosensory feedback for voice F 0 control - Charles R. Larson; Kenneth W. Altman; Hanjun Liu; Timothy C. Hain (Experimental Brain Research, 2008)

Instructing subjects to make a voluntary response reveals the presence of two components to the audio-vocal reflex - Timothy C. Hain; Theresa A. Burnett; Swathi Kiran; Charles R. Larson; Shajila Singh; Mary K. Kenney (Experimental Brain Research, 2000)